Impact of Early Nutrition on the Development of Childhood Obesity (Medical Forum Monthly, 2024)
Objective: To assess the effects of nutrition during earliest childhood on subsequent obesity among children and to determine specific food types that are likely to be linked to obesity.Study Design: A Cross-sectional observational study.Place and Duration of Study: This study was conducted at the Department of Pediatrics, Peoples university of Medical Health Sciences Nawab Shah from05 July 2023 to 05 December 2023Methods: One hundred children in duration of 2- 5 years of age were observed in current research. The data regarding early nutrition, breastfeeding and infant feeding practices, and dietary was derived from questionnaire. The body mass index percentiles were used in determination the level of obesity. Data analysis for this study was done using the SPSS with the hypothesis set at 0.05 (α = 0.05).Results: Out of 100 children, it was found that 30 percent of children were obese. The difference in the mean BMI was significant between users of sugary drinks brought before the age of 7 months and those who were not, with a standard deviation of 2.5, p=0.03. Exclusive breast feeding was significantly related to a 25% reduction in obesity ( p value = 0.02). Early nutrition was established to be a possible risk factor for childhood obesity in the course of the study.Conclusion: Multiple interventions such as feeding practices during infancy and the consumption of sugars in their initial years all are potential roots of Article as child obesity. Breastfeeding support and decrease in the intake of sugary products could therefore be used to cushion obesity amongst children.